2007
DOI: 10.1016/j.exer.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C γ mutations in the C1B domain cause caspase-3-linked apoptosis in lens epithelial cells through gap junctions

Abstract: Failure to control oxidative stress is closely related to aging and to a diverse range of human diseases. We have reported that protein kinase C γ (PKCγ) acts as a primary oxidative stress sensor in the lens. PKCγ has a Zn-finger C1B stress switch domain, residues 101-150. Mutation, H101Y, in the C1B domain of PKCγ proteins causes a failure of the PKCγ oxidative stress response (Lin and Takemoto (2005) (100 μM, 3 h) activated a caspase-3 apoptotic pathway in the lens epithelial cells but was more severe in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Because gap junctions are used in cell-tocell communication pathways, PKCγout mice display learning deficits, insensitivity to pain, do not develop tolerance to alcohol like normal mice ( Abeliovich, et al, 1993), and are more sensitive to hydrogen peroxide induced cataract formation (Lin, 2006). It is thought that these deficits are partially a result of the improper control of gap junctions due to loss of PKCγ (Lin, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Because gap junctions are used in cell-tocell communication pathways, PKCγout mice display learning deficits, insensitivity to pain, do not develop tolerance to alcohol like normal mice ( Abeliovich, et al, 1993), and are more sensitive to hydrogen peroxide induced cataract formation (Lin, 2006). It is thought that these deficits are partially a result of the improper control of gap junctions due to loss of PKCγ (Lin, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among potential deregulated therapeutic targets, Hspa5 (i), Limk2 (ii), Mcl1 (iii), and Gja8 were all found to be upregulated by Igf1 and Pacap. Inhibition of Gja8 by 18alpha-glycyrrhetinic acid [35] and activation of Hspa5 by salubrinal, 2DG, and NE-100 [36,37] have already been shown to support cell survival. Similarly, treatment with LIMKi and A-1210477, two selective inhibitors of Limk2 and Mcl1, respectively, prevents apoptosis in cancer [38,39].…”
Section: Cellular Processesmentioning
confidence: 99%
“…PKCγ SCA-14 mutant plasmid construction and transfection C-terminal EGFP-tagged PKCγ SCA14 mutants (H101Y, S119P, or G128D) were generated previously [18]. In addition, PKCγ SCA14 mutant cDNA was cloned into the pCMVHA vector (Clontech, California) to generate N-terminal HA-tagged PKCγ SCA14 mutants by introducing 5'EcoRI and 3'KpnI sites.…”
Section: Cell Culturesmentioning
confidence: 99%
“…We have previously demonstrated that lens epithelial cells with PKCγ SCA14 mutants (H101Y, S119P, or G128D) lack PKCγ enzyme activity even when endogenous PKCγ is present [18]. This dominant negative effect on endogenous PKCγ has been linked to failure of control of gap junctions and this causes cells to be more susceptible to H 2 O 2 -induced, caspase-3-dependent cell apoptosis [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation